1998
DOI: 10.3181/00379727-217-44216
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Antineoplastic Action of Somatostatin Analogs

Abstract: Abstract. Over the past decade, impressive antineoplastic activity of somatostatin analogs has been demonstrated in many tumor models. More recent research has provided information regarding mechanisms underlying the antiproliferative and apoptosis-inducing actions of these compounds. These include both 'direct' mechanisms that are sequellae of binding of somatostatin analogs to somatostatin receptors present on neoplastic cells and 'indirect' mechanisms related to effects of somatostatin analogs on the host. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
126
0
7

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(137 citation statements)
references
References 36 publications
4
126
0
7
Order By: Relevance
“…It reminds us of the early evidence that somatostatin analogues could inhibit the proliferation of somatostatin receptor-negative neoplasm. 9 These results suggest that octreotide may indirectly affect tumor growth through inhibition of release of some peptides or growth factors such as insulin, EGF and IGF-1, which promote tumor proliferation. 26 Although octreotide could inhibit the growth of gastric adenocarcinoma, the inhibition rate (60.6%) for gastric xenografts treated by octreotide alone 8 was also much lower than the result of rofecoxib plus octreotide in vivo with the same animal model, drug doses and schedules.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…It reminds us of the early evidence that somatostatin analogues could inhibit the proliferation of somatostatin receptor-negative neoplasm. 9 These results suggest that octreotide may indirectly affect tumor growth through inhibition of release of some peptides or growth factors such as insulin, EGF and IGF-1, which promote tumor proliferation. 26 Although octreotide could inhibit the growth of gastric adenocarcinoma, the inhibition rate (60.6%) for gastric xenografts treated by octreotide alone 8 was also much lower than the result of rofecoxib plus octreotide in vivo with the same animal model, drug doses and schedules.…”
Section: Discussionmentioning
confidence: 90%
“…6,7 Various studies have demonstrated that the growth of normal cells and malignant tumor may be regulated by gut peptides. 8,9 In the stomach, besides the known inhibitory function of somatostatin (SST) on acid secretion, it has been suggested that the analogues of SST could be candidates for arresting the growth of gastric adenocarcinoma. Previous data from the literature have shown that the mean tumor volume in nude mice treated with octreotide, an analogue of SST, was significantly lower than that of control group with an inhibitory rate of 60.6%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because somatostatin receptors are widely distributed in the gastrointestinal tract and other tissues, 11,22,29 concerns were raised that therapy with radionuclide somatostatin analogues or AN-238 may produce some side effects. However, in early studies with radiolabeled somatostatin analogues, no or only low-grade toxicity was observed in patients at doses resulting in objective responses.…”
Section: Discussionmentioning
confidence: 99%
“…Page 4 of 22 A c c e p t e d M a n u s c r i p t 4 Somatostatin analogs show antineoplastic activity in a variety of experimental models in vivo and in vitro (Schally 1988;Pollak,Schally 1998;Weckbecker et al, 1993) . They inhibit the growth of various cancer cell lines, such as those of gastric, lung, colorectal, prostatic, ovarian, kidney, brain or thyroid origin (Keri et al, 1996;Weckbecker et al, 1993;Froidevaux, Eberle 2002;.…”
Section: Antitumor Actions Of Somatostatin Analogsmentioning
confidence: 99%